2006
DOI: 10.2737/rmrs-gtr-182
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative capacity, problem framing, and mutual trust in addressing the wildland fire social problem: An annotated reading list

Abstract: We reviewed, annotated, and organized recent social science research and developed a framework for addressing the wildland fire social problem. We annotated articles related to three topic areas or factors, which are critical for understanding collective action, particularly in the wildland-urban interface. These factors are collaborative capacity, problem framing, and mutual trust. The integration of these is a prerequisite of collective action to develop Community Wildfire Protection Plans, reduce vegetative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 43 publications
(14 reference statements)
0
16
0
Order By: Relevance
“…There has been a recent proliferation of studies linking wildland fire planning and management to trust Brooks et al 2006;Cohn et al 2008;Jakes et al 2007;Liljeblad et al 2009;Paveglio et al 2009;Toman et al 2006;Vaske et al 2007). Several case studies have found trust to be a strong predictor of respondents' approval of government agencies to make proper decisions about the use of various treatments, such as prescribed burning and mechanical fuel reduction (Vogt et al 2005;Winter et al 2004).…”
Section: Trust In the Context Of Wildland Firementioning
confidence: 96%
See 1 more Smart Citation
“…There has been a recent proliferation of studies linking wildland fire planning and management to trust Brooks et al 2006;Cohn et al 2008;Jakes et al 2007;Liljeblad et al 2009;Paveglio et al 2009;Toman et al 2006;Vaske et al 2007). Several case studies have found trust to be a strong predictor of respondents' approval of government agencies to make proper decisions about the use of various treatments, such as prescribed burning and mechanical fuel reduction (Vogt et al 2005;Winter et al 2004).…”
Section: Trust In the Context Of Wildland Firementioning
confidence: 96%
“…If one government agency or special interest group dominates the framing of risk and the actions to reduce it, the public will likely be unwilling to trust the process or outcome. Whether the CWPPs allow for and encourage this broader framing of risk is of particular significance since it can lead to the likelihood for broad social and political acceptability of the plan (Brooks et al 2006). …”
Section: Trust In the Context Of Wildland Firementioning
confidence: 98%
“…This presents unique challenges for land managers, particularly in light of competing social values, multiple stakeholder interests, and uncertain management outcomes Brooks et al, 2006;Snider et al, 2006). Additionally, differences in the physical environment, stand conditions, the amount and distribution of available fuels, and weather make 'one size fits all' management approaches ineffective .…”
Section: Bark Beetle Fuels and Fire Management Strategiesmentioning
confidence: 97%
“…This emphasis may soon encompass high-elevation subalpine forests as global climate change increases the potential for bark beetle outbreaks and intense wildfires, wildland/urban interfaces expand, and demands on important forest resources rise (Logan and Powell, 2001;Williams and Liebold, 2002;Carroll et al, 2003;Gan, 2003;Breshears et al, 2005;Brooks et al, 2006).…”
Section: Bark Beetle Fuels and Fire Management Strategiesmentioning
confidence: 97%
“…1), we used an issueand-solution-based approach (Desmarais 2006, Comité scientifique sur les enjeux de biodiversité 2010, Grenon et al 2010, Roy et al 2010. With this problem-solving process (Brooks et al 2006, Dennison 2008, Wilshusen and Wallace 2009, the apparently contradictory aspects of the development of plantations within a context of ecosystem management were addressed through perceived issues. The approach served to define ecological issues based on gaps observed between natural and managed forests.…”
Section: Group Of Experts and Issue-and-solution-based Approachmentioning
confidence: 99%